Safety and effectiveness of an herbal decoction (modified Saengmaeksan) in hypertensive patients: Protocol for a real-world prospective observational study - Nahyun Cho; Hobin Moon; Kyung-Min Shin; Byoung-Kab Kang; Jungtae Leem; Changsop Yang (PLoS ONE, 2025)
Objective Hypertension, a common chronic disease, often leads to serious complications. While conventional management relies on antihypertensive drugs, which can cause side effects and adherence issues, alternative treatments like herbal medicine are gaining attention. This study examines the efficacy and safety of modified Saengmaeksan, an East Asian herbal remedy, in treating hypertension. Methods This single-arm, prospective, observational study will be conducted at Kyunghee Bichedam Korean Medicine Clinic from October 23, 2023 to August 30, 2024, enrolling 30 hypertensive patients. Over 12 weeks, participants will undergo 4 visits, receiving modified Saengmaeksan twice daily for 8 weeks, with a subsequent 4-week follow-up. Primary outcome is the change in systolic blood pressure from the baseline to week 8. Secondary outcomes include diastolic blood pressure changes, radial artery tonometry, and quality of life evaluations. Safety assessments will include monitoring hematologic parameters and adverse events. Data will be analyzed using an ANCOVA model for adjusting confounders. Discussion Modified Saengmaeksan has shown potential for lowering blood pressure in clinical settings, supported by animal and cell studies. However, human studies are scarce. This research will employ radial artery tonometry to analyze blood pressure comprehensively, exploring Saengmaeksan’s hemodynamic effects. The study’s goal is to support the approval of modified Saengmaeksan as a hypertension treatment by the South Korean Food and Drug Administration and to promote the industrialization of traditional herbal medicine in managing hypertension. The findings will provide essential data for future clinical research, aiding in feasibility assessments and sample size determinations for randomized controlled trials.